The relationship between family support and the incidence of hypertension in the elderly - Yudho Priyo Utomo; Siswati; Shanti Rosmaharani; Iin Noviana (Journal of Clinical Nursing Studies and Practice, 2025)
The number of older people with hypertension has grown, and they are more likely to experience a repeat. One of the main causes of this is a lack of family support. This study sought to ascertain the association between the prevalence of geriatric hypertension in the prolanis group at UPT Puskesmas Kalipare, Malang Regency, and family support. Correlation analysis with a cross-sectional technique was employed in the research design. There were 75 respondents in the population of PRB and Prolanis patients, and 63 respondents made up the sample. Random sampling was used in the sampling procedure. Hypertension was the dependent variable, and family support was the independent variable. Questionnaires and observations were employed to obtain data. According to the study's findings, the majority of participants (71.4%) experienced inadequate familial support.Instead of hypertension (28.6%), respondents reported having hypertension as much as 71.4%. Family support and the incidence of hypertension in the elderly in the prolanis group of UPT Puskesmas Kalipare, Malang Regency, were found to be related, as evidenced by the Spearman rank correlation test results, which showed a probability value (0.000) significantly lower than the significant standard of 0.05 or (pa). As a result, Ho was rejected and H1 was accepted. There was a very substantial correlation (p<0.001). Family support is crucial, particularly in the areas of emotion, knowledge, and assistance. Clients who receive this assistance may be able to overcome obstacles, boost their self-esteem, and receive consistent treatment.In order to prevent hypertension, health professionals at the Kalipare Health Center UPT, Malang Regency, must encourage the community to support families in controlling their diet and maintaining good health.